Áp dụng quy tắc chia hai căn bậc hai, hãy tính :
230023" id="MathJax-Element-1-Frame" role="presentation" style="border:0px; box-sizing:border-box; direction:ltr; display:inline; float:none; font-size:18px; font-style:normal; font-weight:normal; letter-spacing:normal; line-height:normal; margin:0px; max-height:none; max-width:none; min-height:0px; min-width:0px; padding:0px; position:relative; text-align:left; text-indent:0px; text-transform:none; white-space:nowrap; word-spacing:normal; word-wrap:normal" tabindex="0">2300−−−−√23−−√ = \(\sqrt{\dfrac{2300}{23}}\) = \(\sqrt{100}\) = 10
12,50,5" id="MathJax-Element-2-Frame" role="presentation" style="border:0px; box-sizing:border-box; direction:ltr; display:inline; float:none; font-size:18px; font-style:normal; font-weight:normal; letter-spacing:normal; line-height:normal; margin:0px; max-height:none; max-width:none; min-height:0px; min-width:0px; padding:0px; position:relative; text-align:left; text-indent:0px; text-transform:none; white-space:nowrap; word-spacing:normal; word-wrap:normal" tabindex="0">12,5−−−−√0,5−−−√ = \(\sqrt{\dfrac{12,5}{0,5}}\) = \(\sqrt{25}\) = 5
19212" id="MathJax-Element-3-Frame" role="presentation" style="border:0px; box-sizing:border-box; direction:ltr; display:inline; float:none; font-size:18px; font-style:normal; font-weight:normal; letter-spacing:normal; line-height:normal; margin:0px; max-height:none; max-width:none; min-height:0px; min-width:0px; padding:0px; position:relative; text-align:left; text-indent:0px; text-transform:none; white-space:nowrap; word-spacing:normal; word-wrap:normal" tabindex="0">192−−−√12−−√ = \(\sqrt{\dfrac{192}{12}}\) = \(\sqrt{16}\) = 4
6150" id="MathJax-Element-4-Frame" role="presentation" style="border:0px; box-sizing:border-box; direction:ltr; display:inline-table; float:none; font-size:18px; font-style:normal; font-weight:normal; letter-spacing:normal; line-height:normal; margin:0px; max-height:none; max-width:none; min-height:0px; min-width:0px; padding:0px; position:relative; text-align:left; text-indent:0px; text-transform:none; white-space:nowrap; word-spacing:normal; word-wrap:normal" tabindex="0">6–√150−−−√ = \(\sqrt{\dfrac{6}{150}}\) = \(\sqrt{\dfrac{1}{25}}\) = \(\dfrac{1}{5}\)